Hyperreality and the Mass Production of Destiny: Baudrillardian Simulacra in Never Let Me Go - Selki, Ali (American & British Studies Annual, 2025)
Existing scholarship on Never Let Me Go has primarily engaged with its ethical, philosophical, and socio-political implications, particularly regarding cloning, human rights, and the commodification of life. While critics such as Rachel Carroll and Amit Marcus have examined the novel’s deconstruction of normative discourses on humanity, and Shameem Black has explored its engagement with multiculturalism and globalization, insufficient attention has been given to its postmodern ontological dimensions. This article addresses this critical gap by applying Jean Baudrillard’s theories of hyperreality, simulation, and simulacra to Ishiguro’s dystopian narrative. It argues that Never Let Me Go functions as a meditation on the dissolution of reality, wherein clones exist as third- and fourth-order simulacra — entities that mask the absence of a profound reality. Through an analysis of Hailsham’s institutional mechanisms, the novel’s representations of nostalgia, and the commodification of identity, this study illuminates the ways in which Ishiguro’s work critiques the hyperreal structures that define late capitalist societies. Ultimately, this article demonstrates how Never Let Me Go challenges conventional distinctions between the authentic and the artificial, exposing the mechanisms through which contemporary societies manufacture consent and obscure the erosion of human agency.